Transition algorithm for wide-speed-range operation of sensorless IPMSM drives - Kang, Byeong Gyu; Jeong, Shin Myung; Lim, Young Seol; Lee, June Seok; Lee, Kyo Beum (Journal of the Korean Society for Railway, 2018)
This paper presents a transition algorithm for wide-speed-range operation of sensorless interior permanent magnet synchronous motor (IPMSM) drives. For the low speed range, a continuous high frequency signal is injected to the motor to extract the rotor position by signal processing method using the measure axis. For the middle and high speed range, the rotor position information is estimated using a disturbance observer based on the extended back electro-motive-force (EEMF) model. The previous transition algorithm between two speed ranges is executed at a specific operation point for wide-speed-range operation. However, this transition algorithm can cause speed overshoot during load changes and change the speed transition point due to parameter variations of IPMSM. Therefore, this paper proposes a new and simple weighting function for stable transition operation between two speed ranges. Experiments are carried out to show the effectiveness of the proposed transition algorithm.
Keywords: EEMF model; High frequency signal injection; IPMSM; Railway application; Sensorless control